The preschool teacher as a reflective practitioner - Syslová, Zora (Masaryk University Press, 2019)
The core of the monograph is the topic of the quality of work of a preschool teacher, especially in connection with the qualification requirements for this profession. It seeks answers to the questions: What characterizes the profession of a preschool teacher today and what is its perspective? How to design initial education so that preschool teachers are truly specialists in changing education? When searching for answers to these questions, the author uses a review of previous empirical findings on this topic in comparison with foreign experience. It presents the results of research focused on self/reflection in connection with the pedagogical performance of preschool teachers in selected aspects.